1255. In Vitro Activity of Vancapticin against Methicillin-Resistant Staphylococcus aureus from Periprosthetic Joint Infection. (31st December 2020) - Cho, Hye-Kyung; Karau, Melissa J; Greenwood-Quaintance, Kerryl E; Hansford, Karl A; Cooper, Matthew A; Blaskovich, Mark A; Patel, Robin; Patel, Robin
Abstract: Background: The vancapticins are modified vancomycin derivatives developed by adding membrane targeting motifs to the C -terminus of vancomycin. We determined the in vitro activity of a lead vancapticin candidate against periprosthetic joint infection-associated methicillin-resistant Staphylococcus aureus (MRSA) in the planktonic and biofilm states, and the effect of adding 0.002% polysorbate 80 (P-80; Sigma-Aldrich) on vancapticin susceptibility testing. Methods: Thirty-seven clinical isolates of MRSA collected at Mayo Clinic (Rochester, Minnesota) were studied. Vancapticin minimum inhibitory concentrations (MICs) were determined using Clinical and Laboratory Standards Institutes guidelines. Minimum biofilm bactericidal concentrations (MBBCs) were determined using a pegged lid microtiter plate assay. Vancapticin MIC and MBBC values were assessed with and without P-80. Vancapticin, vancomycin, and dalbavancin biofilm time-kill assays were performed using biofilms formed by 10 MRSA isolates on Teflon coupons. Results: Vancapticin MICs with and without P-80 ranged from 0.015 to 0.12 μg/mL and 0.25 to 1 μg/mL, respectively. Vancapticin MBBCs with and without P-80 ranged from 0.25 to 4 μg/mL and 1 to 8 μg/mL, respectively. Reductions of biofilm bacterial densities on Teflon coupons after 8 and 24 hours of incubation with vancapticin, vancapticin with P-80, vancomycin, or dalbavancin with P-80 were less than 3-log10 cfu/cm 2 for all isolates tested. Conclusion: Vancapticin has promising in vitro activity against planktonic MRSA and MRSA in a pegged lid biofilm assay, but was not bactericidal against biofilms on Teflon coupons. P-80 decreased vancapticin MICs and MBBCs. Disclosures: Mark A. Blaskovich, PhD, MAB Consulting (Consultant)The University of Queensland (Employee, Grant/Research Support, Other Financial or Material Support, Inventor on patent) Robin Patel, MD, Accelerate Diagnostics (Grant/Research Support)CD Diagnostics (Grant/Research Support)Contrafect (Grant/Research Support)Curetis (Consultant)GenMark Diagnostics (Consultant)Heraeus Medical (Consultant)Hutchison Biofilm Medical Solutions (Grant/Research Support)Merck (Grant/Research Support)Next Gen Diagnostics (Consultant)PathoQuest (Consultant)Qvella (Consultant)Samsung (Other Financial or Material Support, Dr. Patel has a patent on Bordetella pertussis/parapertussis PCR issued, a patent on a device/method for sonication with royalties paid by Samsung to Mayo Clinic, and a patent on an anti-biofilm substance issued.)Selux Dx (Consultant)Shionogi (Grant/Research Support)Specific Technologies (Consultant)